THE INTERRELATIONSHIP OF JAVANESE AND ISLAMIC VALUES ON EDUCATIONAL ASPECTS AND ECONOMIC ASPECTS - Muh Syauqi Malik; Maslahah Maslahah (UIN Walisongo Semarang, 2021)
The relationship between Islam and Javanese culture can be said to be two sides of an inseparable currency. On the one hand, Islam that came and developed in Java is influenced by Javanese culture or culture, while on the other hand, Javanese culture is increasingly enriched by Islamic customs. It makes the fusion between Javanese and Islamic culture stronger to form interrelation, especially in education and economics, a fundamental aspect of human life. Research based on this reference study needs to be done because there has not been any other research that discusses the interrelation of Javanese and Islamic values in the aspects of education and economics in detail. This study uses a qualitative approach to library studies to find, sort, and search for reference sources from ISBN books, national journal articles, and other reference sources to strengthen the analysis. Data analysis includes data reduction, data presentation, conclusion drawing, and verification. The results showed that Islam and Javanese culture have an inseparable relationship. Islamic acculturation with Javanese culture is to implement Islamic sharia with Javanese cultural packaging. The interrelation of Javanese and Islamic values in Education, namely the emergence of pesantren education and da'wah, was conducted by Walisongo to spread religion in the archipelago by combining Javanese and Islamic cultures Shariah. Interrelation Javanese and Islamic values in the economic aspect that is people identify themselves as people who uphold the noble and cultural qualities that they have both geographically and anthropologically, with the economic principles of Javanese people are noble.